368PGenomic analysis of malaysian breast cancers unravel molecular differences from Caucasian breast cancers. (24th November 2019) - Teo, S-H; Zabidi, M; Pan, J W; Ng, P S; Meng, M Y; Hasan, N; Sandey, B; Yip, C H; Rajadurai, P; Rueda, O; Caldas, C; Chin, S F
Abstract: Background: Breast cancer is the leading cause of cancer death among women, and incidence in Asia is increasing in large part because of changes in reproductive and lifestyle factors. Several appreciable differences exist between breast cancers in Asian and Caucasian women. For example, Asians have a younger median age of incidence and correspondingly, a higher prevalence of hereditary factors, and together, these suggest that they may be crucial differences at the molecular level. Methods: We performed whole exome sequencing (WES) on 576 Malaysian breast cancers (at median coverage 75X) and their matched normal blood (40X) to detect single nucleotide variations (SNVs) and small insertions and deletions (indels). We also performed shallow whole genome sequencing (sWGS) to detect major chromosomal aberrations, and transcriptomic sequencing (RNA-seq) to measure gene expression. Results: We captured known copy number changes, together with major breast cancer genes and their phenotypes, for example high frequency of SNVs in hotspot regions in PIK3CA and indels in GATA3. Interestingly, Malaysian breast cancer show higher prevalence of Her2+ molecular subtypes and TP53 mutations, as well as higher immune scores compared with Caucasian breast cancer cases, consistent with previous findings in other smaller Asian datasets. Conclusions: Our report of the hitherto largest dataset of genomic profiling of Asian breast cancers show the molecular differences between Asian and Caucasian breast cancers and point to potential differences in therapy and outcome. Legal entity responsible for the study: Cancer Research Malaysia. Funding: Cancer Research Malaysia, Medical Research Council Newton Ungku Omar Fund, Scientex Foundation, Estee Lauder Breast Cancer Campaign, Yayasan Sime Darby, Yayasan Petronas. Disclosure: All authors have declared no conflicts of interest.